Microtubule-Stabilizing Agents as Potential Therapeutics for Neurodegenerative Disease - Brunden, Kurt R. (2013)
Microtubules (MTs)(), cytoskeletal elements found in all mammalian cells, play a significant role in cell structure and in cell division. They are especially critical in the proper functioning of post-mitotic central nervous system neurons, where MTs serve as the structures on which key cellular constituents are trafficked in axonal projections. MTs are stabilized in axons by the MT-associated protein tau, and in several neurodegenerative diseases, including Alzheimer’s disease, frontotemporal lobar degeneration, and Parkinson’s disease, tau function appears to be compromised due to the protein dissociating from MTs and depositing into insoluble inclusions referred to as neurofibrillary tangles. This loss of tau function is believed to result in alterations of MT structure and function, resulting in aberrant axonal transport that likely contributes to the neurodegenerative process. There is also evidence of axonal transport deficiencies in other neurodegenerative diseases, including amyotrophic lateral sclerosis and Huntington’s disease, which may result, at least in part, from MT alterations. Accordingly, a possible therapeutic strategy for such neurodegenerative conditions is to treat with MT-stabilizing agents, such as those that have been used in the treatment of cancer. Here, we review evidence of axonal transport and MT deficiencies in a number of neurodegenerative diseases, and summarize the various classes of known MT-stabilizing agents. Finally, we highlight the growing evidence that small molecule MT-stabilizing agents provide benefit in animal models of neurodegenerative disease and discuss the desired features of such molecules for the treatment of these central nervous system disorders.